Some Considerations on The History Of Human Settlement In The Natural-Geographical Regions Of Uzbekistan - Eshchanov Hurmat Matnazarovich (Web of Scientist International Scientific Research Journal, 2025)
This study explores the history of human settlement in the natural-geographical regions of Uzbekistan, focusing on the ethnogenesis and cultural development of various ethnic groups. The research aims to analyze historical sources and archaeological findings to trace settlement patterns and socio-economic transformations. The methodology includes a historical and comparative approach, utilizing archaeological, anthropological, and geological data. Key studies by researchers such as B.Ye. Bijanov, Ye.A. Vinogradov, and M.A. Itina provide insights into settlement activities from the Neolithic to the Bronze Age. Excavations in regions such as Ustyurt, Khorezm, and the Zarafshan Valley reveal evidence of economic adaptation, migration, and ethno-integration processes.The results highlight how geographical factors influenced human settlement, with nomadic and sedentary populations shaping distinct cultural traditions. Findings suggest that environmental changes, such as shifting river courses, played a crucial role in population movements and settlement structures. The study concludes that Uzbekistan's historical landscape was shaped by continuous interactions between various ethnic groups, contributing to the region’s rich cultural heritage